O-004 Balloon guide catheter improves recanalisation, procedure time, and clinical outcomes with Solitaire in acute stroke: analysis of the NASA Registry. (14th July 2013) - Nguyen, T; Malisch, T; Castonguay, A; Gupta, R; Sun, C; Martin, C; Holloway, W; Mueller-Kronast, N; Linfante, I; Dabus, G; Marden, F; Bozorgchami, H; et al.
Abstract : Introduction: Efficient and timely recanalisation is an important goal in acute stroke endovascular therapy. Several studies have shown improved recanalisation and clinical outcomes with the Stentriever devices compared to the MERCI device. The goal of this study was to evaluate the role of the balloon guide catheter and recanalisation success in a sub-study of the North American Solitaire Stent-Retriever Acute Stroke Registry (NASA). Methods: The investigator-initiated NASA Registry recruited 24 clinical sites in North America to submit demographic, clinical, site-adjudicated angiographic and clinical outcome data on consecutive patients treated with the Solitaire FR device (Covidien). Balloon guide catheter was used at the discretion of the treating physicians. Results: There were 354 patients included in this study. Data of BGC use was not reported in 16 patients, leaving 338 patients in this sub-analysis, of which 149 (44%) had placement of the BGC. Mean age was 67.3+15.2 years and median NIHSS was 18. Patients with BGC had more hypertension (82% vs 73%; p=0.05), atrial fibrillation (51% vs 33%; p=0.001) and were more commonly administered tPA (51% vs 39%; p=0.02) compared to patients without BGC. Time from symptom onset to groin puncture and number of passes were similar between the two groups. Procedure time was shorter in patients with BGC (120 vs 161 minutes, p=0.02) and less rescue therapy was used in patients with BGC (20% vs 28.6%, p=0.05). TICI 2b/3, TICI 3 recanalisation was higher in patients with BGC compared to patients without (TICI 2b/3: 75% vs 70%; TICI 3 53% vs 32.5% p>0.001). Distal emboli and emboli in new territory were similar between the two groups. Discharge NIHSS (mean 12 vs 17.5; p=0.002) and good clinical outcome at 3 months were superior in patients with BGC compared to patients without (51.6% vs 35.8%; p=0.02). In multivariate analysis, initial NIHSS, use of general anaesthesia and BGC were independent predictors of good clinical outcome. Conclusion: Use of a balloon guide catheter with the Solitaire Stent retriever in acute ischaemic stroke results in superior recanalisation results, faster procedure time, decreased need for rescue therapy, and improved clinical outcome. Disclosures: T. Nguyen: 2; C; Penumbra, THERAPY Trial DSMB/ CEC. T. Malisch: None. A. Castonguay: None. R. Gupta: None. C. Sun: None. C. Martin: None. W. Holloway: None. N. Mueller-Kronast: None. I. Linfante: None. G. Dabus: None. F. Marden: None. H. Bozorgchami: None. A. Xavier: None. A. Rai: None. A. Badruddin: None. M. Taqi: None. M. Abraham: None. H. Shaltoni: None. V. Janardhan: None. A. Abou Chebl: None. P. Chen: None. A. Yoo: None. R. Nogueira: None. A. Norbash: None. O. Zaidat: None.